Product market integration and environmental policy coordination in an international duopoly - Straume, Odd Rune (2006)
We analyse the effect of product market integration on environmental policy incentives in an international duopoly, where national policy makers act strategically. If traditional trade policy instruments are not available, environmental policies will typically be determined by the interaction of conflicting policy incentives. Contrary to popular belief, we find that international product market integration, in this particular setting, might reduce the need for transnational policy coordination, both from a purely environmental and from a social welfare perspective.